PROBLEMS OF TEACHING MEDIA TEXTS TO C1 LEVEL STUDENTS (Scientific journal of the Fergana State University, 2023)
In this article, we have discussed the problems of teaching media texts to C1 level students. Newspapers, periodicals, television, films, radio, computer software and the Internet are just a few examples of media texts that are covered in English classes. Understanding and interpreting media requires a high level of English proficiency equivalent to level C1 on the European grading scale (CEFR). But the problem of teaching, methods and approaches of media texts to C1 level students has not yet been studied. This article considers the problems within this frame.